Relationship between pore size distribution and shear strength of soil - Priono. (2012)
Numerous research works have been performed on bimodal soil, but those studies are generally limited to soil-water characteristic curve (SWCC) and permeability of soil. Therefore, this project investigates the relationship between SWCC, pore size distribution (PSD) and shear strength of soils with a bimodal grain-size distribution. Lower air-entry value in the first subcurve of SWCC (AEV1) indicates a larger size of dominant macropore whereas lower air-entry value in the second subcurve (AEV2) implies a larger dominant micropore in PSD. Fitting equation of bimodal SWCC should not only produce high R2, but also has physical meaning which is important to describe characteristics of bimodal SWCC. For matric suctions less than AEV1, relationship between shear strength and matric suction is linear and ϕb is equal to ϕ’. When matric suction is in between AEV1 and AEV2, linear relationship between shear strength and matric suction can still be observed but ϕb is less than ϕ’. On the other hand, relationship between shear strength and matric suction is not linear anymore and ϕb is much smaller than ϕ’ for matric suctions beyond AEV2. Goh et al. (2010) model was modified to predict the shear strength of bimodal soils for matric suction beyond AEV1 more accurately.